Large Mesenchymal Hepatic Hamartoma in Pediatric Age: A Case Report - Alhasan H. Alhebshi; Ammar Kabbarah; Murad Aljiffry (Case Reports in Surgery)
Benign liver tumors are infrequently observed in the pediatric age group, with an incidence reported at 0.7 per million population annually. Among these tumors, mesenchymal hamartoma constitutes 18%–29%. Imaging studies commonly reveal a well-marginated, solitary mass, often measuring up to 30 cm. The mass, primarily located in the right liver lobe (75% of cases), may exhibit a pedunculated structure. We present a case of a 1-year-and-9-month-old boy diagnosed with hepatic mesenchymal hamartoma. A contrast-enhanced computed tomography of the abdomen and magnetic resonance imaging (MRI) were performed and demonstrated a large multiloculated septated liver lesion measuring approximately 13.6 × 17.7 cm, demonstrating multiple partially thickened internal septations. The procedure was done for the patient in the form of an extended right hepatectomy with segment 4A and cholecystectomy.